Not just money: What mothers value in conditional cash transfer programs in India - Rao, Krishna D.; Kachwaha, Shivani; Kaplan, Avril; Bishai, David (BMJ, 2020)
Introduction: Conditional cash transfers (CCTs) have become an important policy tool for increasing demand for key maternal and child health services in low/middle-income countries. Yet, these programs have had variable success in increasing service use. Understanding beneficiary preferences for design features of CCTs can increase program effectiveness.